2006
DOI: 10.1248/bpb.29.380
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Hybrid Liposomes for Human Breast Tumor Cells along with Activation of Caspases

Abstract: It is well known that liposomes are used as drug carriers: examples are antitumor agents, hormones, and immunomodulation. 1,2) On the other hand, we have recently produced specific hybrid liposomes composed of vesicular and micellar molecules; they are stable for a longer period. The physical properties of these liposomes such as size, membrane fluidity, phase transition temperature, and hydrophobicity can be controlled by changing the constituents and compositional ratios of hybrid liposomes. 3,4) In the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It has been already elucidated that hybrid liposomes induce apoptosis in various tumor cells, with activations of caspases-3, -8, and -9, and reduction of mitochondria membrane potential. 8,[11][12][13]16 HL-n could probably fuse and accumulate into HCT116 cells, and induce apoptosis through activation of caspase cascades.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been already elucidated that hybrid liposomes induce apoptosis in various tumor cells, with activations of caspases-3, -8, and -9, and reduction of mitochondria membrane potential. 8,[11][12][13]16 HL-n could probably fuse and accumulate into HCT116 cells, and induce apoptosis through activation of caspase cascades.…”
Section: Dovepressmentioning
confidence: 99%
“…Inhibitory effects of hybrid liposomes composed of L-α-dimyristoylphosphatidylcholine (DMPC) and polyoxyethylene (20) sorbitan monolaurate (Tween 20) including antitumor drugs such as 1,3-bis(2-chloroethyl)-1-nitrosourea on the growth of glioma cells in vitro and in vivo have been observed. 5 On the other hand, hybrid liposomes composed of DMPC and polyoxyethylene(n) alkyl ethers without any drugs demonstrated remarkable inhibitory effects on the growth of various tumor cells in vitro [6][7][8] and in vivo. [9][10][11][12] In addition, it has been demonstrated that hybrid liposomes could induce apoptotic cell death in leukemia, 13 hepatoma, 7 lung cancer, 14 breast cancer, 8 and primary effusion lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical properties of HL such as shape, size, membrane fluidity of phase transition can be controlled by changing the constituents and compositional ratio. Remarkably high inhibitory effects of HL composed of DMPC and polyoxyethylene(n) dodecyl ethers (C 12 (EO) n ) on the growth of tumor cells in vitro [13][14][15][16][17], in vivo [17][18][19][20][21], and clinical application [22][23][24] have been obtained without drugs. We have reported HL induced apoptosis in various cancer cells including NSCLC (A549, H460, H23 and H520) cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…5) With respect to the role of Ca 2ϩ in inhibition of cellular proliferation, it has been reported that Ca 2ϩ imported into the cytoplasm of mammalian cells could lead to a programmed cell death "apoptosis" through several signalling pathways. 6,7) However, the mechanistic details of tumor-specific growth inhibition effects of Ca On the other hand, we have investigated the membrane targeted chemotherapy with hybrid liposomes 8,9) composed of phospholipids and nonionic surfactants for tumor cells in vitro, [10][11][12][13][14][15] in vivo, 15,16) and in clinical applications. 16,17) Significantly, the denaturation of cell membranes by hybrid liposomes could lead to apoptosis in tumor cells without any drugs.…”
mentioning
confidence: 99%